Freshwater influx, hydrographic reorganization and the dispersal of ice-rafted detritus in the sub-polar North Atlantic Ocean during the last deglaciation - Small, David; Austin, William; Rinterknecht, Vincent (Journal of Quaternary Science, 2013)
International audience